Determinantes da cotonicultura brasileira e os efeitos dos choques de oferta e demanda, de 1990 a 2013 - Buhse, Ana Paula (2015)
The general purpose of this work is to analyze the general determinants of cotton production and the evolution of Brazilian cotton production from 1990 to 2013. Period in which the sector has undergone changes, and trade liberalization and deregulation in the market resulted in the entry of the foreign product with the highest quality causing crisis in the production of Brazilian cotton. However, with further technological incentives in the late 1990s it was possible to increase the commodity productivity resulting in the recovery, making the country among the leading manufacturers and exporters in the 2000s. To make the analysis was utilized the theoretical model of Blanchard and Quah (1989), but adapted by Barros et al. (2006) for agriculture and Alves, Barros e Bacchi (2008) for cotton. The results showed that it is the supply shocks (area and productivity) contributing to explain the export variations, averaging 40% of changes in exports is explained by area, with a significant contribution because the variable itself accounts for about 38% of its variations, and the variable productivity explains around 5%. Compared with the growth of production, it follows that the domestic price and productivity explain about 30% and 8% from the fourth year, respectively. Finally, we have as a conclusion that you need a period of adjustment to the decision to plant or not, taking into account the area, production and past prices and / or prospects for the next harvest.